Cash Expenditure Accounting Information System Operational Cost Driver At the Fleet Department of PT Cipta Krida Bahari Banjarmasin - Isnawati; Hikmahwati; Nailiya Nikmah (Indonesian Journal of Applied Accounting and Finance, 2022)
This study aims to describe the driver's operating cash disbursement accounting information system at the Fleet Section of PT Cipta Krida Bahari Banjarmasin. This study uses a qualitative descriptive approach related to the driver's operating cash disbursement accounting information system. The results showed that the Accounting Information System for Cash Expenditures for Driver Operational Costs at the Fleet Section of PT Cipta Krida Bahari Banjarmasin has interrelated functions, namely the commercial sales function, operation function, driver function, fleet admin function, fleet leader function, and manager function, and financial functions. Procedures for disbursing driver operational costs include procedures for ordering goods by customers, procedures for submitting travel costs, procedures for disbursing or transferring travel costs, and procedures for recording travel costs. The documents used in the cash disbursement system for the driver's operational costs are travel documents, PUO, DA, manifest, SIJK, BBM notes, manifest, and TCA. The records used are FAST system, Cash Advance application, TCA website, MCM system, Middleware system, Ramco system, and enterprise system.